Plugawe i orgiastyczne święto miłości? Sobótka w ujęciu Jana Kochanowskiego - Maciejewska, Anna (2022)
Noc swietojanska (Midsummer night) is associated with the very distant times when the sun and water wereworshipped. At that time the Slavs paid special attention to astronomical phenomena resulting from the Earth’srotation around the Sun. The time of the summer solstice appeared to be a time of great celebration, as evidenced bythe wide range of nomenclature defining the entirety of these rites: Kupalnocka, Kupala, noc swietojanska or Sobótka.It is also very likely that this celebration has become a Christian equivalent of the pre-existing cult of a pagan deity,as evidenced by, for example, numerous Midsummer rites: clapping, playing, singing, dancing, jumping around thefire, girding oneself with mugwort. Performing night dances, singing and pairing up became the basis not only foraccusations by preachers that pagan idols were being glorified, but it even began to arouse anxiety among moralists,who considered the above-mentioned acts debauched. Although Catholics and Protestants tried to combat thecustoms related to the sobótka, Jan Kochanowski decided to maintain these folk traditions.
Keywords: Kochanowski, Jan